Participation of a Non-Disputing Party in Arbitration and Protection of the Public Interest before an ICSID Tribunal - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
The paper discusses the need to protect the legitimacy of decision-making process in investment arbitration through public access to the proceedings. Unlike commercial arbitration, investment arbitration entails decisions on state responsibility for measures directed towards protection of environment, lives and health of its population or human rights. Presence of the public interest in such disputes brings under the strong criticism a traditional characteristic of arbitration process – its confidentiality. The problem of democratic deficit of decision-making can be resolved, inter alia, by allowing persons who are not parties to the dispute to participate in the proceedings if they consider that their interest might be affected by arbitral award. The 2006 Arbitration Rules of International Centre for Settlement of Investment Disputes envisage, subject to approval of the Tribunal, the right of a non-disputing party to file a written submission with the Tribunal regarding a factual or legal issue connected with the subject matter of the dispute. However, without right of those entities to attend arbitral hearings and, more importantly, without their access to documents submitted during the proceedings, this is not by far enough to give “friends of the court” a meaningful and significant role.